THE DEVELOPMENT OF E-MODULES PROBLEM BASED LEARNING USING GOOLE CLASSROOM FOR BASIC ELECTRICITY AND ELECTRONICS AT VOCATIONAL SCHOOL - Hengraini Eka Putri; Usmeldi Usmeldi (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2020)
The purpose of this research is to produce a valid e-modules problem based learning using Google Classroom practical, and effective in basic electricity and electronics subjects. This e-modules problem based learning using Google Classroom is designed to improve student’s understanding so that it can improve students learning outcomes. The method in this study uses Research and Development (R&D) with 4-D development procedures (Define, Design, Develop, Desseminate). The data of analysis technique uses descriptive analysis techniques to describe the validity, practicality, and effectiveness of e-modules problem based learning using Google Classroom. The results obtained of this development research: The validity of e-modules problem based learning using Google Classroom is declared valid on the media and material aspects. The practicality of e-modules problem based learning using Google Classroom from teacher and student responses is stated to be very practical. The effectiveness of e-modules problem based learning using Google Classroom is stated to be effective in improve to learn the outcomes. Based on the findings of this study it is concluded that the e-modules problem based learning using Google Classroom is valid, practical, and effective to be used as a learning aid in basic electricity and electronics subjects.